From a Fan to a Stalker: The Spectrum of Fan Attitudes in Korean Culture Industry - Lewandowska, Marta (Literatura Ludowa. Journal of Folklore and Popular Culture, 2022)
The article characterizes three fannish attitudes among South Korean audience of popular culture – the True Fan, the Ani-Fan and the Saseang (Obsessive Fan) by discussing fan activities and practices. The author puts particular emphasis on the Korean music industry, and its top-down way of structuring and manipulating the fan-object of affection as well as intra-fandom relationships through enforcing models of behavior and interaction with idols among fans. The category of parasocial relationship is key to this analysis as central to Korean pop culture industry; other concepts discussed include bottom-up and top-down practices and Deleuze’s rhizomatic concept of culture, especially fitting for a discussion concerning the fan niche system found in South Korea as well as the interactions between the fandom and the pop culture industry.